The Effect Of Employee Engagement and Corporate Culture on Job Satisfaction at PT. Oemah Insan Mandiri - Pramana Agus Sumardianto; Ahmad Mardalis (Al-Kharaj: Journal of Islamic Economic and Business, 2023)
The purpose of this study is to analyze the effect of employee engagement and corporate culture on job satisfaction, so the researcher will take the title "The Effect of Employee Engagement and Corporate Culture on Job Satisfaction at PT Oemah Insan Mandiri". This research uses quantitative methods.Â  This study uses primary and secondary data. Data was obtained through respondents' answers using a closed questionnaire type. The population in this study was 120 employees of PT Oemah Insan Mandiri. The sampling technique in this study was nonprobability sampling. The data collection method used in this study was the distribution of questionnaires. The questionnaire was made using a Likert scale format with a frequent scale. The data analysis technique in this study uses Partial Least Square (PLS) using the help of SMARTPLS software. The results of this study show that employee engagement affects job satisfaction, and corporate culture affects job satisfaction.